Teachers’ Perception Towards Local Content-Based English Materials of Speaking Skill for Young Learners - Ruth Nova Mandaria; Elanneri Karani; Joni Bungai (General English Education, 2022)
As one of the most significant communication skills that one is required in the digital era, it is necessary to develop speaking skills among young learners who learn English at elementary school earlier. However, English was not the primary subject for Elementary students, especially in State Elementary schools. So, it made the English teachers have difficulty finding suitable textbooks for students. This article details the findings of a study conducted to learn more about the needs of young English learners in primary schools in the digital age. Four Elementary English teachers in Palangka Raya participated in the study. The study instruments were a questionnaire and interview guide. The survey results are revealed using percentages and qualitative descriptions. The findings will be utilized to create and develop an English e-book (based on local material) for young learners studying English at the elementary level.